Conversion of unripe coconut husk into refined products using humidified air in packed bed gasification column - Ram M.; Mondal M.K. (My University, 2025)
High amount of solid wastes are produced because of growing consumption of coconut water. Such biomass wastes should be recycled for reducing the accumulation of trash, adding value to the supply chain and generating profits. Steam gasification of these wastes may be a promising process to increase the H2 and decrease CO, CH4 and CO2 content in fuel gas. The present work demonstrates an alternative process for gasification of unripe coconut husk to yield hydrogen-rich fuel gas using humidified air. The effect of various parameters like gasification temperature, equivalence ratio, humidity of air and size of the unripe coconut husk on fuel gas composition was studied. The unripe coconut husk was analyzed with TGA, CHNS, FTIR, and ED-XRD techniques. Furthermore, fuel oil was also accessed with FTIR and GC-MS analysis. Moles of H2 in fuel gas was found to increase from 7.67 to 10.26 for air and humidified air gasification, respectively at relative humidity of 95% and gasifying temperature 800 °C. © 2019, Springer-Verlag GmbH Germany, part of Springer Nature.